Long‐term loss to follow‐up in the TREAT Asia HIV Observational Database ( TAHOD ) - Jiamsakul, Awachana; Kiertiburanakul, Sasisopin; Ng, Oon Tek; Chaiwarith, Romanee; Wong, W.; Ditangco, R.; Nguyen, K.V.; Avihingsanon, A.; Pujari, S.; Do, C.D.; Lee, M.P.; Ly, P.S.; et al. (Wiley, 2019)
Objectives: With earlier antiretroviral therapy (ART) initiation, time spent in HIV care is expected to increase. We aimed to investigate loss to follow-up (LTFU) in Asian patients who remained in care 5 years after ART initiation. Methods: Long-term LTFU was defined as LTFU occurring after 5 years on ART. LTFU was defined as (1) patients not seen in the previous 12 months; and (2) patients not seen in the previous 6 months. Factors associated with LTFU were analysed using competing risk regression. Results: Under the 12-month definition, the LTFU rate was 2.0 per 100 person-years (PY) [95% confidence interval (CI) 1.8–2.2 among 4889 patients included in the study. LTFU was associated with age > 50 years [sub-hazard ratio (SHR) 1.64; 95% CI 1.17–2.31] compared with 31–40 years, viral load ≥ 1000 copies/mL (SHR 1.86; 95% CI 1.16–2.97) compared with viral load < 1000 copies/mL, and hepatitis C coinfection (SHR 1.48; 95% CI 1.06–2.05). LTFU was less likely to occur in females, in individuals with higher CD4 counts, in those with self-reported adherence ≥ 95%, and in those living in high-income countries. The 6-month LTFU definition produced an incidence rate of 3.2 per 100 PY (95% CI 2.9–3.4 and had similar associations but with greater risks of LTFU for ART initiation in later years (2006–2009: SHR 2.38; 95% CI 1.93–2.94; and 2010–2011: SHR 4.26; 95% CI 3.17–5.73) compared with 2003–2005. Conclusions: The long-term LTFU rate in our cohort was low, with older age being associated with LTFU. The increased risk of LTFU with later years of ART initiation in the 6-month analysis, but not the 12-month analysis, implies that there was a possible move towards longer HIV clinic scheduling in Asia. © 2019 British HIV Association